Masa Jabatan Pimpinan Organisasi Profesi Advokat melalui Keputusan Mahkamah Konstitusi RI - Paet Hasibuan; Muhammad Nurul Azmi; Fauziah Lubis (Departement of Mathematics Education, 2023)
The 1945 Constitution of the Republic of Indonesia stipulates explicitly that Indonesia is a state based on law. In a constitutional state (rechtsaat) the state recognizes and protects the human rights of every individual. In a contstiutional state,everyone must be treated equally before the law (equality before the law). The principle of rule of law in the life of society and the state requires the role of an advocate as an independent and free profession. So that this freedom result in the absence of laws governing advocate. However, previously Article 38 of Law number 14 of 1970 had indicated the need to regulate the advocate profession in a separate law. After the law on advocate, namely Law No. 18 of 2003 does not yet clearly stipulate the term of office for the heads of advocate organizations. Therefore, the existence of a law that regulates the term of office for the leadershp of an advocate organization is very important in order to provide comfort and peace among fellow advocate professions.